2018
DOI: 10.1038/s41467-018-04058-2
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of virus assembly and organization by the measles virus matrix protein

Abstract: Measles virus (MeV) remains a major human pathogen, but there are presently no licensed antivirals to treat MeV or other paramyxoviruses. Here, we use cryo-electron tomography (cryo-ET) to elucidate the principles governing paramyxovirus assembly in MeV-infected human cells. The three-dimensional (3D) arrangement of the MeV structural proteins including the surface glycoproteins (F and H), matrix protein (M), and the ribonucleoprotein complex (RNP) are characterized at stages of virus assembly and budding, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
78
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 61 publications
10
78
1
Order By: Relevance
“…A previous study of MARV budding has shown that filamentous particles constituted infectious virions while rounded particles of lower infectivity were released during late rounds of infection (Welsch et al, 2010). This morphological distinction has also been observed in the paramyxovirus RSV using cryo-ET in the presence of a fusion inhibitor to exclude the possibility of observing fusion events (Ke et al, 2018a). The particles are observed in various stages of the budding process including initiation, elongation, and scission.…”
Section: Virus Buddingmentioning
confidence: 67%
See 2 more Smart Citations
“…A previous study of MARV budding has shown that filamentous particles constituted infectious virions while rounded particles of lower infectivity were released during late rounds of infection (Welsch et al, 2010). This morphological distinction has also been observed in the paramyxovirus RSV using cryo-ET in the presence of a fusion inhibitor to exclude the possibility of observing fusion events (Ke et al, 2018a). The particles are observed in various stages of the budding process including initiation, elongation, and scission.…”
Section: Virus Buddingmentioning
confidence: 67%
“…This study notes that each virion typically has only one conformation of F protein on its surface, but differences can be seen between virions. Another study goes further to suggest that the F protein is exclusively in the prefusion form on filamentous particles but in the postfusion form on spherical particles (Ke et al, 2018a). This observation suggests that the infectious form of the virus is the filamentous form and highlights the need for studying virions in their most native form, free from purification artefacts, that is by cryo-ET of budding sites on the cell surface (see Section 5).…”
Section: Inherently Pleomorphic Virions and Their Glycoproteinsmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, while the ability to elucidate the structures of pleomorphic, multi-subunit complexes in native, in situ cellular environment is a major advantage of cryo-ET and STA over other structural techniques, current STA processing strategies are typically only successful for highly ordered, symmetrical, homogenous samples that have limited conformational variations, and are present in high copy numbers within a single tomogram ( Figure 1b). Examples of such complexes include purified viruses and associated viral complexes 17,25,[27][28][29]31,33,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] , highly-abundant cytoplasmic and membrane-associated ribosomes 9,10,19,35,[53][54][55][56][57][58][59][60][61][62] , and axonemal dynein motors . Large, eukaryotic and bacterial membrane-associated complexes have also benefited greatly from this technique, as alignment of the relatively high-signal membrane bilayer can help drive the initial alignment of the more noisy, low SNR complex of interest.…”
Section: Introductionmentioning
confidence: 99%
“…The viral structural proteins include surface proteins hemagglutinin (HN) and fusion (F), which act as an attachment factor and fusion machinery respectively (13). The matrix protein (M) lines the inner membrane of the virion and is important for bridging the interactions between HN, F and vRNP complexes, and this interaction drives membrane curvature which results in the budding of virions (14, 15). In order for virion release to occur at the membrane, cytoplasmic viral genome and structural proteins must be transported to the cell surface.…”
Section: Introductionmentioning
confidence: 99%